FPGA based Single Channel Analyzer (SCA) used for nuclear radiation counting system - Begum, Mohaimina (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Master of Electrical and Electronic Engineering, 2015.